Towards a New Paradigm for Statistical Evidence - Bhatti, Muhammad Ishaq; Kim, Jae H. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Many scientists now widely agree that the current paradigm of statistical significance should be abandoned or largely modified. In response to these calls for change, a Special Issue of Econometrics (MDPI) has been proposed. This book is a collection of the articles that have been published in this Special Issue. These seven articles add new insights to the problem and propose new methods that lay a solid foundation for the new paradigm for statistical significance.